Підвищення фізичної підготовки юних легкоатлетів за допомогою бар’єрних вправ - Добринський, В.; Мудрик, Ж.; Dobrynskiy, V.; Mudryk, Z. (Східноєвропейський національний університет ім.Лесі Українки, 2012)
Проаналізовано систему підготовки спортивних резервів. Вивчено динаміку мотивів до занять спортом юних бігунів на середні дистанції. Проведено самооцінку фізичної підготовки спортсменів протягом педагогічного експерименту. Досліджено вплив спеціальних бар’єрних вправ на покращення навчально-тренувального процесу, фізичної підготовки й підвищення мотивації юних спортсменів до занять спортом The analysis of the system of preparation of sport reserves has been conducted. The dynamics of reasons of young runners on midranges who are going in for sports have studied. The self-appraisal of physical preparation during a pedagogical experiment has been done. The influence of the special hurdle exercises for the improvement of educational-training process and the increasing of young sportsmen’s motivation to go in for sports and the improvement their physical preparation have investigated.
The Increasing of Young Athletes’ Physical Preparation by Hurdle Exercises
Keywords: система підготовки; бар’єрні вправи; мотив; фізична підготовка; самооцінка; system of preparation; hurdle exercises; reason; physical preparation; self-appraisal